Minimally invasive tricuspid valve surgery without caval occlusion: Short and midterm results. Issue 2 (5th January 2021) - Margari, Vito; Malvindi, Pietro G.; De Santis, Adriano; Kounakis, Giorgio; Visicchio, Giuseppe; Mastrototaro, Giuseppe; Dambruoso, Pierpaolo; Carbone, Carmine; Paparella, Domenico
Abstract: Objective: The use of minimally invasive or transcatheter interventions rather than standard full sternotomy operations to treat tricuspid valve (TV) disease is increasing. The debate however is still open regarding venous drainage management during cardiopulmonary bypass (CPB) and wheatear or not superior and inferior vena cava should be occluded during the opening of the right atrium to avoid air entrance in the venous line. The aim of the present study is to report operative outcomes and midterm follow‐up results of minimally invasive TV surgery performed without caval occlusion. Methods: A retrospective outcome evaluation from institutional records was performed with prospective data entry. Considered were consecutive patients who underwent right mini‐thoracotomy TV surgery isolated or combined with mitral valve surgery during the period from June 2013 to February 2020. A telephone and echocardiographic follow‐up was performed. Results: During the study period, 68 consecutive patients underwent minimally invasive TV surgery without occlusion of cava veins. The mean age was 69 ± 14 years and 48 (70%) were female. All operations were performed safely without air‐lock during CPB. A perioperative cerebral stroke occurred in one patient. The survival at a 5‐ and 8‐year follow‐up was 100% and 79%, respectively. No severe tricuspid regurgitation was evident at echocardiographic follow‐up. Conclusion: Our results show that performing tricuspid surgery without caval occlusion is safe. The air was captured by the active vacuum drainage system without causing damage. Midterm follow‐up data confirm that a minimally invasive approach does not alter the quality of surgery.